Hubungan Status Gizi dan Asupan Lemak dengan Kebugaran pada Anggota UKM Futsal - Arum Kusumaning Ttyas; Nur Lathifah Mardiyati (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
Physical fitness affects the performance of futsal players and is influenced by nutritional status and fat intake. Balanced nutritional status is important for athletes because malnutrition can reduce the body's ability to transport oxygen. Fat also acts as a long-term energy source in addition to glycogen, which is used to produce ATP during activity or exercise. The aim was to determine the relationship between nutritional status and fat intake with fitness in members of the University's futsal UKM in Surakarta. This observational study used a cross-sectional design with 51 male respondents who were active members of the futsal UKM, selected through the convenience sampling method. Inclusion criteria included willingness to be respondents, male gender, as an active member, and no history of disease. While exclusion criteria included athletes who withdrew before the study was completed, and athletes who withdrew from the futsal UKM. The results showed that members had a thin/lack nutritional status of 15.7%, overweight of 7.8%, and obesity of 13.7%. then low-fat intake of 60.8% and excess fat intake of 17.6%. The fitness level was very poor as much as 39.2%, poor and sufficient as much as 25.5%. The results of this study showed no significant relationship between nutritional status and fat intake with fitness (p = 0.322; r = -0.141 and p = 0.233; r = 0.170). This study is expected to be useful as a reference for further research.